(untitled) (PJDOL, 2023)
This study was initiated to conceptualize the concept of distance mode of learning and its possible initiative at university of Haripur with special reference to its rationale, significance and challenges. 23 Tutors and 57 students of Teachers’ training programs offered by Allama Iqbal Open University (AIOU), Islamabad, Sarhad University of Science and Technology (SUIT) Peshawar and University of Peshawar wereconsulted.